Electrochemical Study of Thallium(I) in Thiamine Hydrochloride and Pyruvate and Simultaneous Determination of it with Some Metal Ions - Aboul-Kasim, Ensaf (Asian Journal of Chemistry, 2010)
The polarographic behavior of thallium(I) has been studied using thiamine hydrochloride and pyruvate as complexing agents at constant ionic strength (0.1 mol dm–3 NaNO3). At the dropping mercury electrode, thallium(I)-pyruvate or thiamine chelate ions give a single well-defined reversible wave both d.c. and a.c. polarographically, and the rate of reduction is diffusion controlled. Thallium(I) is found to form 1 : 1 metal to ligand complex with both ligands, and this composition is supported by the conductometric titration. The formation constant values have been calculated. Pyruvate and thiamine were used as the supporting electrolytes for the a.c. polarographic determination of thallium with lead or copper, cadmium and selenium simultaneously.